Design, development and validation of Food Frequency Questionnaires for the diabetic population: protocol for a systematic review and meta-analysis - José C Fernández-Cao; Estefania Aparicio (BMJ Open, 2022)
Introduction The Food Frequency Questionnaire is one of the most widely used tools for estimating nutritional intake in epidemiological studies. No study has been systematically performed to comprehensively explore Food Frequency Questionnaires designed, developed and validated specifically for the diabetic population (FFQs-DDV-DiaP). Therefore, a systematic review and meta-analysis will be carried out in order to identify and describe FFQs-DDV-DiaP; to examine their design, development, validity and reproducibility; as well as to estimate the overall degree of correlation and agreement; and to evaluate the factors that affect them.Methods and analysis A systematic literature review will be performed in PubMed/MEDLINE, Scopus and Web of Science to find potentially relevant studies. Original studies related to the design, development, as well as the assessment of the validity and reproducibility of FFQs-DDV-DiaP; reported in English or Romance languages will be selected. Independent reviewers will select studies, extract relevant data and assess FFQs-DDV-DiaP quality. Data will be pooled using the generic inverse-variance method with random-effects models and expressed as correlation coefficients or mean differences with 95% CIs to examine the global validity and reproducibility of FFQs-DDV-DiaP. Heterogeneity will be evaluated by the Cochran Q-statistic and quantified by the I2 statistic. Stratified analyses and random-effects meta-regressions will be performed to explore heterogeneity and whether any covariate influences the effect sizes. Finally, publication bias will be assessed through the Begg’s and Egger’s tests.Ethics and dissemination This systematic review and meta-analysis will not use confidential personal data. Therefore, the requirement of ethical approval or informed consent is not necessary. The results of this review will be disseminated only in peer-reviewed publications or at relevant scientific conferences.PROSPERO registration number CRD42021268575.